Odprta vprašanja vročanja v praksi - Voglar, Matjaž (Pravni letopis, 2010)
The latest amendments to Slovenian Civil Procedure Act have changed the service of process in many aspects. However, despite the simplifications of procedure, several unsettled questions remain. The choice between personal and "ordinary" service of process can be problematic in practice. This has lead to some courts' decision to always use personal service, which is more reliable and offers more procedural guarantees to the parties. Other practical issues include service to legal persons and other registry subjects, service to lawyers, service via employer, service into P.O. Box, and service to persons whose actual residence is unknown. Concerning the latter, the Constitutional Court of Slovenia annulled the part of legislation allowing service of process at the "address for delivery" regardless to where the party actually lives. Consequently, the courts now have to initiate the procedure of determining the actual residence of the absent person, which is performed by administrative organs.
Keywords: Administrative procedure; civilno pravo; procesno pravo; sodišča; sodne odločbe; upravni postopek